THE CONTENT OF LIQUIDITY COMMERCIAL BANKS - Путінцева, Тетяна (Socio-economic relations in the digital society, 2019)
The article includes approaches to determining the nature of liquidity commercial banks. The importance of providing liquidity is indicated. The degree of liquidity issues in general and the liquidity of commercial banks partly has been analyzed and critically evaluated in the economic literature. Moreover, existing of liquidity interpretations are clarified. The most of definitions characterize of liquidity commercial banks as a certain stock of liquidity or cash flow. The author’s explanation about nature of liquidity commercial banks is given. The author proposed the classification of types liquidity commercial banks. There is description of commercial bank's assets. Furthermore, the relation between liquidity and solvency of commercial banks isconsidered. Besides, factors that open out liquidity of commercial banks have been clarified. In the article, going is analyzed near interpretation of term «liquidity of bank» after different scientists in the cut of economic signs. The article discusses of managing the liquidity of a commercial bank. There are essence, purpose, methods of management and regulation of liquidity are determined. Recommendations about management of the bank’s liquidity, which improves the bank’s efficiency are offered. In addition, the article analyzes the main  theoretical and methodological features of banks’ liquidity management in current conditions. The features of liquidity from this inception to modern appearance are considered. Result is defined. The basic concepts, essence and value of liquidity for banks, necessity of its regulation and management are defined.There are principles which give the main tools of operation management og liquidity. And also the liquidity of a commercial bank is largely determined by such qualitative factors as the structure and stability of the resource base.
Keywords: liquidity; solvency; classification of types liquidity; factors of liquidity; commercial bank